Actitudes y comportamientos de riesgo para trastornos de la conducta alimentaria en jóvenes universitarios, Colombia (2015)
ABSTRACT: To determine the attitudes and behaviors associated with body image and therefore to Eating Disorders (EDs) among students attending Universidad de Antioquia (Colombia). Methods: The size of the sample was composed of 267 students (125 men and 142 women), belonging to the low, middle and high socioeconomic classes (n = 92, 99 and 76, respectively). Multivariate analysis of variance (MANOVA) with orthogonal-type canonical contrast, factor analysis, multiple correspondence analysis and dimensional-type frequency analysis were used. To do this, the information collected through a survey according to the discriminating factors gender and socioeconomic class was analyzed. Results: A highly significant difference between genders regarding the concept of corporal condition was found. Similarly, statistical differences between socioeconomic classes (p < 0.0001) was also found. Conclusions:.There are differences in body image perceptions between social class and gender: while men judge and generate pressure on women because of their physical appearance, women, try to control food intake, follow diets and go through slimming treatments, among others, which possibly shows that women perceive the pressure of comments and of the environment they live in and, therefore, they adopt health risk behaviors in order to achieve and maintain a slim figure and gain acceptance.